Methods to improve our field - Hill, Aaron D.,; McKenny, Aaron F.,; O'Kane, Paula,; Paroutis, Sotirios, (Research methodology in strategy and management ;, 2023)
Research Methodology in Strategy and Management advances understanding of the methods used to study organizations - including managers, strategies, and how firms succeed. Offering innovative ideas that explore how strategy and management methodology can be developed, the chapter authors in Volume 14, Methods to Improve Our Field, consider approaches that range from the re-imagining of secondary data in the digital age and Interpretive Phenomenological Analysis (IPA) to Machine Learning and Artificial Intelligence. Methods to Improve Our Field is a necessity for both academics and researchers interested in the progression and cutting-edge studies of management, strategy, international business, entrepreneurship, and organization theory.